China$1 (Bs Gas Development Strategiess - Centre, Shell; Development Research Center, The (Cham Springer Nature, 2017)
energy transition; energy policy; China; hydrocarbon strategy; low carbon
English
Keywords: Environmental economics; energy transition; energy policy; China; hydrocarbon strategy; low carbon